Analisis Kepemimpinan Soft Firm Dan Budaya Organisasi Dalam Meningkatkan Kinerja Tim Duta Print - Haura Nasywa Habenula; Ardista Dwi Elsania; Hanum Salsabila Hassa; Muhammad Nabil Al Abrori; Sendy Fatikasari; Mar’atus Sania (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2025)
This study aims to analyze how soft-firm leadership and organizational culture contribute to improving team performance at Duta Print, a printing business involving employees with diverse backgrounds, personalities, and work habits. Key issues identified include differences in communication skills, variations in employee responses to instructions, challenges in dealing with customers with diverse personalities, and the need to adapt to work pressure. This study used a descriptive qualitative approach through in-depth interviews and observations of operational processes to obtain a comprehensive picture of teamwork dynamics. The results indicate that a soft-firm leadership style, combining gentle interpersonal approaches with responsibility-based assertiveness, creates a family-like work environment while maintaining discipline. Furthermore, an organizational culture that emphasizes two-way communication, mutual reminders, and a receptive attitude to criticism contributes to the formation of an adaptive and stable team. In the context of customer service, communication skills, patience, and adapting speaking styles have proven to be key skills for dealing with diverse customer personalities. These findings indicate that integrating adaptive leadership and a supportive organizational culture is an effective solution for improving team performance in small businesses.